2008
DOI: 10.25011/cim.v31i4.4783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a seashell protein Haishengsu on cell growth and expression of apoptosis genes in leukemia K562 cells

Abstract: Objectives: To investigate the effect of a seashell protein Haishengsu (HSS), an extract from a shellfish Tegillarca granosa, on cell growth and the expression of apoptosis genes in leukemia K562 cells. Methods: Cultured K562 cells were treated with HSS at various concentrations (10-40mg/L). The cell cycle, cell growth and the expression of apoptosis suppressor gene bcl-2 and apoptosis promoting gene bax were evaluated. Results: HSS, 20mg/L, inhibited cell cycle in the G0/G1 and S phases. HSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…It has a molecular weight of approximately 15 kDa but an unknown chemical structure. HSS was found to have a potent suppressive effect on several types of tumor cells in vivo and in vitro [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It has a molecular weight of approximately 15 kDa but an unknown chemical structure. HSS was found to have a potent suppressive effect on several types of tumor cells in vivo and in vitro [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies found that HSS causes apoptosis and suppress cell growth at the G0/G1 and S phases of the K562 cell cycle. 4 Our recent study also demonstrated that with adriamycin-resistant K562/ADM cells, HSS also increased the rate of apoptosis. 12 In addition, HSS reduced the expressions of pglycoprotein, a drug-resistance inducing protein in leukemia and other cells.…”
Section: Discussionmentioning
confidence: 93%
“…[1][2][3] Recently, we found that HSS suppressed the growth of leukemia K562 cell by inhibiting the G0/G1 and S phases of the cell cycle. 4 HSS also induced apoptosis in these leukemia cells by reducing the expression of apoptosis suppressor bcl-2, and increasing the expression of apoptosis promoting bax. 4 The in vivo anticancer effects of HSS have been investigated in two small clinical trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HSS was also tested against MDR K562/ADR cells, and it induced apoptosis at 20 mg/l [178]. HSS also inhibited K562 cells at G0/G1 and S phase and lowered Bcl-2 and enhanced Bax levels ( Figure 2) (Table 6) [179].…”
Section: Saponinsmentioning
confidence: 99%